2021
DOI: 10.3390/cells10040764
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoproteins and the Kidney

Abstract: Dyslipidemia is a typical trait of patients with chronic kidney disease (CKD) and it is typically characterized by reduced high-density lipoprotein (HDL)-cholesterol(c) levels. The low HDL-c concentration is the only lipid alteration associated with the progression of renal disease in mild-to-moderate CKD patients. Plasma HDL levels are not only reduced but also characterized by alterations in composition and structure, which are responsible for the loss of atheroprotective functions, like the ability to promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 94 publications
0
11
2
3
Order By: Relevance
“…Smoking was reported in 9.5% of our study patients who had CKD progression, with a 2.8-fold increased risk for CKD progression; studies have reported that smoking is significantly associated with a higher risk of CKD and smoking is strongly associated with CKD progression [ 45 , 46 ]. Obesity and HDL cholesterol were not significantly associated with CKD progression in this study unlike findings from other studies where patients who had obesity and/or hyperlipidaemia had higher rates of CKD progression [ 47 , 48 ]. This difference could be due to the high prevalence of obesity/overweight in both progressor and non-progressor groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Smoking was reported in 9.5% of our study patients who had CKD progression, with a 2.8-fold increased risk for CKD progression; studies have reported that smoking is significantly associated with a higher risk of CKD and smoking is strongly associated with CKD progression [ 45 , 46 ]. Obesity and HDL cholesterol were not significantly associated with CKD progression in this study unlike findings from other studies where patients who had obesity and/or hyperlipidaemia had higher rates of CKD progression [ 47 , 48 ]. This difference could be due to the high prevalence of obesity/overweight in both progressor and non-progressor groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Smoking was reported in 9.5 % of our study patients who had CKD progression, with a 2.8-fold increased risk for CKD progression; studies have reported that smoking is significantly associated with a higher risk of CKD and smoking is strongly associated with CKD progression (42, 43). Obesity and HDL cholesterol were not significantly associated with CKD progression in this study unlike findings from other studies where patients who had obesity and/or hyperlipidaemia had higher rates of CKD progression (44, 45). This difference could be due to the high prevalence of obesity/overweight in both progressor and non-progressor groups.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, renal defficiency was defined as an eGFR < 90 mL/(min·1.73 m 2 ), as renal damage and related dyslipidemia have already started in early stages of chronic kidney disease [ 22 ]. Chronic kidney disease is known to be an independent risk factor for cardiovascular disease, so it is reasonable to assume that with renal insufficiency in the picture, the size shifting of HDL particles, which reflects only an imbalance in HDL metabolism, is no longer a strong predictor of the severity of coronary heart disease [ 23 , 24 ]. In coronary heart patients with renal insufficiency, the protective effects of larger HDL particles may be weakened; thus, lipid-targeting therapy may not be as essential in these patients.…”
Section: Discussionmentioning
confidence: 99%